2013
DOI: 10.7314/apjcp.2013.14.10.5929
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of ICAM-1 and β3 Integrin Gene Variations in Patients with Brain Tumors

Abstract: Background: Primary brain tumors constitute a small percent of all malignant cancers, but their etiology remains poorly understood. β3 integrin (ITGB3) has been recognized to play influential roles in angiogenesis, tumor growth and metastasis. Intercellular adhesion molecule-1 (ICAM-1) is a surface glycoprotein important for tumor invasion and angiogenesis. The aim of this study was to investigate whether specific genetic polymorphisms of ICAM-1 and ITGB3 could be associated with brain cancer development and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…[1] showed that ICAM-1 plays an important role in tongue squamous cell carcinoma progression, which may result from the cancer cell activity, tumour angiogenic activity, lymphangiogenic activity, and increased macrophage/cancer cell adhesion. Similar results were also reported for colon carcinoma cases and in brain tumours [6, 9, 13]. The increased expression of adhesion molecules on tumour cells correlated with higher cancer progression and worse prognosis.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…[1] showed that ICAM-1 plays an important role in tongue squamous cell carcinoma progression, which may result from the cancer cell activity, tumour angiogenic activity, lymphangiogenic activity, and increased macrophage/cancer cell adhesion. Similar results were also reported for colon carcinoma cases and in brain tumours [6, 9, 13]. The increased expression of adhesion molecules on tumour cells correlated with higher cancer progression and worse prognosis.…”
Section: Discussionsupporting
confidence: 86%
“…In many studies the relationships between ICAM-1 polymorphisms and increased incidence of carcinomas with different origin, e.g. brain and oral cavity, have been established [9, 10]. Interestingly, in the case of lung cancer, colon cancer, melanoma, glioblastoma, primary liver cancer, or multiple myeloma an increase of soluble forms of ICAM-1 and VCAM-1 (sICAM-1, sVCAM-1) levels in blood correlated with a higher clinical and morphological tumour stage [1, 3, 6, 8, 1113].…”
Section: Introductionmentioning
confidence: 99%
“…The abnormal expression of ITGA2 has been correlated with unfavorable prognoses in multiple types of cancer. The nucleotide polymorphisms affecting adhesive molecules have been associated with the risk and prognosis of astrocytoma tumors (51).…”
Section: Discussionmentioning
confidence: 99%
“…Cancer has an important and increasing role in the total disease load in the world (Thakkar et al, 2014). Cancer is regarded as onehistology (Mehta et al, 2011;Yilmaz et al, 2013). The brain like any other tissue of the body can bear neoplastic changes, but in the brain even benign neoplasms can cause complications as malignant tumors and this is because of the particular physiology and anatomy of the central nervous system (Sayegh et al, 2014).…”
Section: Introductionmentioning
confidence: 99%